Lessons from the Past: Some Histories of Alpha-1 Antitrypsin Deficiency Before Its Discovery. (2nd January 2018) - Perciaccante, A.; Charlier, P.; Negri, C.; Coralli, A.; Appenzeller, O.; Bianucci, R.
ABSTRACT: A1AT deficiency- a genetically inherited autosomal codominant disease with more than 120 identified alleles- was first identified by Laurell and Eriksson in 1963. The most common hereditary disorder in adults, A1AT causes an increased risk of developing pulmonary emphysema and liver disease. In A1AT patients, lung disease generally presents at a younger age than "usual" chronic obstructive pulmonary disease (COPD) and it may be misdiagnosed as asthma. Because A1AT deficiency patients can show the same clinical features as non-deficient COPD (including increased evidence of bronchiectasis, frequent exacerbations, impaired health status and a degree of reversibility of airflow obstruction), the World Health Organization recommend to test every patient with a diagnosis of COPD or adult-onset asthma for A1AT deficiency. Despite these recommendations, the epidemiology of A1AT deficiency remains uncertain. Although recently discovered A1AT deficiency has affected human populations since antiquity. By using scientific data and recently studied skeletons and historical cases, we show that it is now possible to reconstruct the natural history of pathological processes, whether due to genetic, infectious or environmental factors. We believe that the evolution of disease in patients and research to elucidate the relationship between social science and environmental are pertinent contemporaneous subjects.